Pengaruh Pengetahuan Keuangan, Financial Confidence, dan Moderasi Sumber Pendapatan terhadap Perilaku Keuangan Karyawan Swasta - Joshua Tiento; Muhadjir Anwar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The pace of change in the era of globalization has brought the world economy including Indonesia to develop very rapidly. These developments affect the human mindset to follow trends that occur and will lead to consumptive financial behavior. Financial behavior related to the use of wages earned by the community is used more to meet their consumption needs than to save. This study aims to analyze the effect of Financial Knowledge and Financial Confidence on Financial Behavior with Source of Income as a moderating variable. The population in this study are private employees in the city of Surabaya. The sampling technique used purposive sampling method with determining the number of samples calculated using the slovin formula and producing a total of 100 respondents. The data collection technique used a questionnaire which was then carried out by data analysis techniques using Partial Least Square (PLS). The results of this study indicate that: (1) Financial Knowledge has a significant positive effect on Financial Behavior, (2) Financial Confidence has a significant positive effect on Financial Behavior, (3) Source of Income has a non-significant effect in moderating the effect of Financial Knowledge on Financial Behavior, (4) Source of income has a significant negative effect in moderating the effect of Financial Confidence on Financial Behavior.